Impact of Patient Age on Clinical Efficacy and Toxicity of Checkpoint Inhibitor Therapy - Wong, Selina K.; Nebhan, Caroline A.; Johnson, Douglas B. (Frontiers in Immunology, 2021)
The addition of immune checkpoint inhibitors (ICIs) to the therapeutic armamentarium for solid malignancies has resulted in unprecedented improvements in patient outcomes in many cancers. The landscape of ICIs continues to evolve with novel approaches such as dual immune checkpoint blockade and combination therapies with other anticancer agents including cytotoxic chemotherapies and/or antiangiogenics. However, there is significant heterogeneity seen in antitumor responses, with certain patients deriving durable benefit, others experiencing initial benefit followed by acquired resistance necessitating change in therapy, and still others who are primarily refractory to ICIs. While generally better tolerated than traditional cytotoxic chemotherapy, ICIs are associated with unique toxicities, termed immune-related adverse events (irAEs), which can be severe or even lethal. As a disease of aging, older individuals make up a large proportion of patients diagnosed with cancer, yet this population is often underrepresented in clinical trials. Because ICIs indirectly target malignant cells through T cell activation, it has been hypothesized that age-related changes to the immune system may impact the efficacy and toxicity of these drugs. In this review, we discuss differences in the clinical efficacy and toxicity of ICIs in patients at the extremes of age.